2013
DOI: 10.4067/s0718-95162013005000007
|View full text |Cite
|
Sign up to set email alerts
|

Influence of genotype and harvest year on polyphenol content and antioxidant activity in murtilla (Ugni molinae Turcz) fruit

Abstract: Polyphenol content and antioxidant activity in murtilla (Ugni molinae Turcz) fruit from three genotypes (the 14-4 genotype and the Red Pearl-INIA and South Pearl-INIA varieties) were studied over five growing seasons. Our results showed significant differences in total polyphenol content among yearly harvests. The lowest value (283 ± 72 mg GAE/100 g dw) was obtained for the 14-4 genotype in the 2008 harvest, and the highest value (2,152 ± 290 mg GAE/100 g dw) was observed for the variety South Pearl-INIA in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 30 publications
2
39
0
Order By: Relevance
“…The significant differences in antioxidant levels between the two varieties of sea-buckthorn were probably due to the varietal characteristics, as the plants were grown under the same conditions of climate and soil. The results as well as other analysis (Alfaro et al, 2013) highlight the importance of genotype as a crucial factor affecting the content of antioxidants in berry plants.…”
Section: Resultsmentioning
confidence: 85%
“…The significant differences in antioxidant levels between the two varieties of sea-buckthorn were probably due to the varietal characteristics, as the plants were grown under the same conditions of climate and soil. The results as well as other analysis (Alfaro et al, 2013) highlight the importance of genotype as a crucial factor affecting the content of antioxidants in berry plants.…”
Section: Resultsmentioning
confidence: 85%
“…Both locations had higher amounts of rainfalls in 2010 than in other investigated years, so it is probable that more available water enabled increased polyphenol and anthocyanin synthesis. Alfaro et al (2013) found a significant positive correlation between rainfalls and total polyphenols in murtilla fruits (Ugni molinae Turcz). Mitić et al (2012) found an influence of season, in particular climatic conditions, on polyphenol and anthocyanin content in sour cherry cvs.…”
Section: Resultsmentioning
confidence: 99%
“…'Murtilla', 'mutilla' or 'murta' (Ugni molinae Turcz) is a native Chilean species that produces a small berry fruit with a recognized fruity, sweet and floral aroma (Scheuermann et al, 2008) and antioxidant activity (Shene et al, 2009;Ruiz et al, 2010;Rubilar et al, 2011;Speisky, López-Alarcón, Gómez, Fuentes, & Sandoval-Acuña, 2012;Alfaro et al, 2013). Polyphenolic compounds have been associated with antioxidant and antimicrobial activity for this native species (Shene et al, 2009;Ruiz et al, 2010;Rubilar et al, 2011;Alfaro et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenolic compounds have been associated with antioxidant and antimicrobial activity for this native species (Shene et al, 2009;Ruiz et al, 2010;Rubilar et al, 2011;Alfaro et al, 2013). Ruiz et allimited range of the commercial dehydrated murtilla fruit, and all products are processed only using freeze drying, such as Murtaberry from Nativ for Life, Chile.…”
Section: Introductionmentioning
confidence: 99%